Effects of Pilates combined with breathing exercise on lung function, body posture and postural stability among female college students: A randomized controlled trial - Jie Zhang; Yanan Zhao; Qianwen Wang (PLoS ONE, 2025)
Objective This study aimed to explore the effects of Pilates combined with breathing exercise on lung function, body posture, and postural stability among female university students. Methods A total of 66 females (mean age 19 years) with poor body posture were recruited from a local university and randomly divided into three groups, Pilates combined with breathing exercise group (PRT), Pilates only group (PLT), and control group (CON). Exercise interventions were conducted three times per week, 60 min per session, and lasted 16 weeks (8 weeks of group training + 8 weeks of self-training). Lung function and respiratory muscle performance, as the primary outcomes were measured using the Lung Function Tester. Secondary outcomes were standing posture and static postural stability. Results Significant group differences were found at post-test in Forced Vital Capacity (FVC) (F(2, 50) = 3.63, p = 0.034, pη2 = 0.13) and Minute Ventilation (MV) (F(2, 50) = 3.52, p = 0.04, pη2 = 0.123), where the PRT group showed more improvements than the PLT group especially in FVC (mean difference = 0.43, p < 0.05). Furthermore, the PRT group showed significant improvements at post-test in Forced Expiratory Volume in 1 second as a percentage of Forced Vital Capacity (FEV1%) (F(2, 42) = 10.2, p < 0.01, pη2 = 0.327), Peak Expiratory Flow Rate (PEFR) (F(2, 42) = 5.62, p = 0.01, pη2 = 0.211) and Tidal Volume (TV) (F(2, 42) = 8.38, p < 0.001, pη2 = 0.285). Additionally, it improved body posture and static postural stability, with notable gains in certain stability measures under both eyes-open and eyes-closed conditions (p < 0.05). Conclusions Combining breathing exercises with Pilates can improve lung function, body posture, and postural stability in female college students, and a longer training duration (> 16 weeks) appears beneficial for achieving optimal outcomes. These findings suggest a potential association between lung function and postural stability mediated by respiratory muscle function, which warrants further investigation.